Experimental Study on Performance of Combined Air-source Heat Pump and Freezer under Frosting Condition - Wu Qiqi; Guo Xianmin; Ding Mingqing (Zhileng xuebao)
A part of the refrigerant of the air-source heat pump (ASHP) system is used for mechanical subcooling of the freezer in the combined air-source heat pump and freezer system. This can improve the performance of the system. In this paper, the outdoor heat exchanger of the ASHP system and condenser of the freezer was designed as an integrated heat exchanger, which can retard the frost formation and growth in winter. The performance of the combined ASHP-freezer under frosting condition was studied experimentally, and the performance of ASHP system and freezer under combined operating conditions was compared with that under separated operating conditions. The performance of the combined system and the frosting characteristics on the outdoor heat exchanger were analyzed under different cooling mass flow ratios. The experimental results indicated that the frosting period of the integrated outdoor heat exchanger under combined working conditions of ASHP-freezer is prolonged as2.17 times as that under separated operating conditions, when the outdoor heat exchanger is severely frosted. The average heating capacity and average COP of the ASHP system under combined working condition were increased by approximately 5% and 4.8%, respectively, when compared with that under separated operating conditions. The average refrigerating capacity and average COP of the freezer increased as the cooling mass flow ratio increased. With respect to the cooling mass flow ratio in the range of 0–12%, the frosting period, average heating capacity, and average COP of the ASHP system slightly changed as the cooling mass flow ratio increased. Conversely, in range exceeding 12% of cooling mass flow ratio, the frosting period was reduced as the cooling mass flow ratio increased, and the average heating capacity and average COP exhibited a downward trend.